Pemberdayaan Masyarakat Melalui Produksi Maggot sebagai Pakan Alternatif Ikan: Kajian Pustaka - Ar-Ridho, Muhammad Naufal (BINA' AL-UMMAH, 2024)
The depletion of fishmeal resources due to overfishing and habitat degradation has become a critical issue for the aquaculture industry, increasing the need for sustainable and cost-effective feed alternatives. This study explores the potential of maggot cultivation as an alternative fish feed and its role in community empowerment. Using a qualitative method with a literature review approach, this research synthesizes findings from various studies on maggot-based feed production, organic waste management, and their socio-economic impacts. The findings reveal that maggots, with their high protein content of 40-60%, equivalent to fishmeal, can significantly enhance fish growth while reducing dependence on conventional feeds. Furthermore, maggot production utilizes organic waste, addressing environmental concerns and promoting a circular economy. Community-level maggot cultivation has proven effective in lowering production costs for fish farmers, creating new economic opportunities, and improving livelihoods, particularly in coastal and rural areas. This study highlights maggot cultivation as a sustainable innovation, offering ecological and economic benefits while fostering community development. The findings advocate for the broader adoption of maggot-based feeds as a viable strategy to address the challenges of aquaculture sustainability and organic waste management.